Current Status and Outlook of Low-Melting-Point Metals in Biomedical Applications - Mao, Jianbin; Kim, Ju Hyung; Seo, Soonmin (Advanced Functional Materials, 2024)
In recent years, low-melting-point metals including liquid metals, exhibiting outstanding physical and chemical properties such as excellent thermal and electrical conductivity, high surface tension, and biocompatibility, have garnered increasing attention from researchers. The melting point of such metals profoundly influences their properties and determines their range of applications, and comprehending the characteristics and properties of low-melting-point metals is crucial for their future applications. Although studies related to liquid metals are growing exponentially in particular, reports exploring the properties and applications of low-melting-point metals from the perspective of the melting point are still in their early stages. This review aims to comprehensively summarize the key properties and relevant applications of current low-melting-point metals described in recent studies, focusing on gallium- and bismuth-based metal alloys. In addition, this review discusses the opportunities and challenges associated with low-melting-point metals, and it is anticipated that this review will contribute to the advancement of low-melting-point materials in the fields of flexible electronics and biomedicine, particularly for biomedical applications.
Keywords: Biomedical applications; Bismuth-based metal alloy; Current status; Eutectic alloys; Gallium-based metal alloy; Low melting point; Metal alloys; Property; Status and outlook; bismuth-based metal alloys; eutectic alloys; gallium-based metal alloys; liquid metals; low melting points